Recent advances in bionic scaffolds for cartilage tissue engineering - Zhang, Yushan; Yu, Weihan (Frontiers in Bioengineering and Biotechnology, 2025)
Articular cartilage is difficult to regenerate. It often leads to osteoarthritis after injury, which seriously affects the quality of life of patients. Presently, the clinical treatments of articular cartilage injury have certain limitations. With the development of tissue engineering, cartilage repair becomes possible. Different types of bionic scaffolds have shown great application potential in cartilage repair. We reviewed the characteristics of ideal bionic scaffolds, including biocompatibility, biodegradability, mechanical and structural properties, bioactivity and functionality. We also summarized the latest research progress of different bionic scaffolds in recent years, hoping to provide a reference for the design of bionic scaffolds with stable performance and definite efficacy, and help them to be gradually applied in clinical practice.